2011
DOI: 10.4236/ojst.2011.12006
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion effect on the flexural strength & micro-hardness of ips e-max ceramics

Abstract: Objectives: The effect of ceramics construction (pressable, machinable) and corrosion on flexural strength and micro-hardness was studied. Materials & Methods: Two types of ceramics were tested: IPS e-max Press and IPS e-max CAD. Forty samples were constructed and divided into 2 groups according to the type of ceramics. Each group was then subdivided into 2 subgroups. Subgroups 1 were not subjected to corrosion while subgroups 2 were subjected to corrosion test. Finally each subgroup was divided into 2 classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…This in turn leads to plaque accumulation, secondary caries, and periodontal inflammation. Corrosion can also lead to discoloration of the restoration and a decrease in fracture strength of the glass-ceramic [13,14,51]. The results of this study demonstrated that SiC coating is an effective approach to improve the chemical stability of glass-ceramic materials by minimizing corrosion and maintaining a smoother surface (Figures 1, 2 and 4).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This in turn leads to plaque accumulation, secondary caries, and periodontal inflammation. Corrosion can also lead to discoloration of the restoration and a decrease in fracture strength of the glass-ceramic [13,14,51]. The results of this study demonstrated that SiC coating is an effective approach to improve the chemical stability of glass-ceramic materials by minimizing corrosion and maintaining a smoother surface (Figures 1, 2 and 4).…”
Section: Discussionmentioning
confidence: 81%
“…This in turn leads to plaque accumulation, secondary caries, and periodontal inflammation. Corrosion can also lead to discoloration of the restoration and a decrease in fracture strength of the glass-ceramic [13,14,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(40) Also, Vickers Hardness Test is a convenient mean for investigating the mechanical properties of small volume materials. (45) Vita Enamic recorded the highest weight loss followed by IPS e.max CAD then Celtra Duo. There was a significant difference between Vita Enamic weight loss and both IPS e.max CAD and Celtra Duo, while there was no significant difference between IPS e.max CAD and Celtra Duo weight loss.…”
Section: Discussionmentioning
confidence: 93%
“…Another report suggested better mechanical properties of polymer-ceramic materials, with less brittleness, better edge stability as well as superior machinability and esthetics [37]. Nguyen et al [38] stated that mechanical properties, including FS, hardness and fracture toughness, were significantly improved in NCRCs using the method of manufacturing pre-polymerized materials under high pressure and high temperature.…”
Section: Discussionmentioning
confidence: 99%